PENGEMBANGAN PERMAINAN BOLA BESAR MELALUI MODIFIKASI PERMAINAN SEPAKBOLA TANGAN - Yulita Yulita; Dwi Qomara (STKIP Melawi, 2019)
Abstract: This study aimed to create a hand football game model that could be used as a guide. 1) create hand football game model game in learning phisical education, sport and health for fifth grade of elementary school student. 2) find out the effectiiveness in the hand football game phisical education, sport and health subject for elementry school students in fifith grade. 3) find out the excitement in the hand football game subject for elementary school students in fifith grade. The research planning consisted of some steps they were. 1 )analyse, 2) develop product, 3) expert validation, 4) field trials, 5) product revision. The result of this study was the hand football game as one of the big ball game lesson. Phisical education, sport and health that is suitable to the characteristics of elementary school students. The hand football game hand giver effective influence on the students in learning. The acceptance of hand foot ball game previewed three aspects they were cognitive. Psychomotor, and affective.Key word: Soccer Hand Ball Playing Abstrak: Penelitian ini bertujuan untuk menghasilkan model permainan sepakbola tangan yang dapat digunakan sebagai panduan 1) menghasilkan suatu model permainan sepakbola tangan dalam pembelajaran Penjasorkes bagi siswa SD kelas V, 2) mengetahui keefektifan dalam permainan sepakbola tangan dalam pembelajaran Penjasorkes bagi siswa SD kelas V, 3) mengetahui ketertrimaan dalam permainan sepakbola tangan dalam pembelajaran Penjasorkes bagi siswa SD kelas V. Metode penelitian yang digunakan adalah penelitian pengembangan model modifikasi permainan bola besar. 1) Melakukan analisis yang akan dikembangkan, 2) Mengembangkan Produk, 3) Validasi Ahli, 4) Uji coba Lapangan, 5) Revisi Produk. Hasil penelitian ini berupa permainan sepakbola tangan sebagai salah satu materi permainan bola besar Penjasorkes yang sesuai dengan karakteristik peserta didik SD, permainan sepakbola tangan telah memberikan pengaruh yang efektif bagi peserta didik dalam pembelajaran Penjasorkes, Keterterimaan produk permainan sepakbola tangan ditinjau dari 3 unsur ranah Penjasorkes yaitu kognitif, psikomotor, dan afektif.Kata Kunci: Permainan Sepak Bola Tangan